Kynurenic Acid Analog Attenuates the Production of Tumor Necrosis Factor-α, Calgranulins (S100A 8/9 and S100A 12), and the Secretion of HNP1–3 and Stimulates the Production of Tumor Necrosis Factor-Stimulated Gene-6 in Whole Blood Cultures of Patients With Rheumatoid Arthritis - Balog, Attila; Varga, Borisz; Fülöp, Ferenc; Lantos, Ildikó; Toldi, Gergely; Vécsei, László; Mándi, Yvette (Frontiers in Immunology, 2021)
Objectives Rheumatoid arthritis (RA) is a chronic, inflammatory joint disease with complex pathogenes involving a variety of immunological events. Recently, it has been suggested that kynurenic acid (KYNA) might be a potential regulator of inflammatory processes in arthritis. KYNA has a definitive anti-inflammatory and immunosuppressive function. The aim of the present study is the complex investigation of the effects of a newly synthetized KYNA analogue – SZR 72 on the in vitro production of TNF-α, TSG-6, calprotectin (SA1008/9), SA100 12 (EN-RAGE), and HNP 1-3 (defensin-α) in the peripheral blood of RA patients in various activities of the disease. Methods The RA patients (n=93) were selected based on the DAS28 score. Peripheral blood samples from 93 RA patients and 50 controls were obtained, and activated by heat inactivated S. aureus. Parallel samples were pretreated before the activation with the KYNA analogue N-(2-N, Ndimethylaminoethyl)-4-oxo-1H-quinoline-2-carboxamide hydrochloride. Following the incubation period (18hr), the supernatants were tested for TNF-α, TSG-6, calprotectin, S100A12, and HNP1–3 content by ELISA. Results SZR 72 inhibited the production of the following inflammatory mediators: TNF-α, calprotectin, S100A12, and HNP1–3 in whole blood cultures. This effect was observed in each group of patients in various phases of the disease. The basic (control) levels of these mediators were higher in the blood of patients than in healthy donors. In contrast, lower TSG-6 levels were detected in RA patients compared to healthy controls. In addition, the KYNA analogue exerted a stimulatory effect on the TSG-6 production ex vivo in human whole blood cultures of RA patients in various phases of the disease. Conclusion These data further support the immunomodulatory role of KYNA in rheumatoid arthritis resulting in anti-inflammatory effects and draw the attention to the importance of the synthesis of the KYNA analogue, which might have a future therapeutic potential.